Incidence of Port Site Infection After Laparoscopic Cholecystectomy: Our Experience at Hayatabad Medical Complex - Rashid Aslam; Farrukh Ozair Shah; Muhammad Alam Alam; Shehzad Akbar Khan (Gandhara University, 2023)
OBJECTIVES This study aimed to assess the factors that affect post-laparoscopic cholecystectomies PSI and determine which characteristics can be changed to prevent PSI in a trial to maximize the benefits of laparoscopic surgery. METHODOLOGY The study included all patients who experienced port site infection following laparoscopic cholecystectomy. All patients received Inj Ceftriaxone 1gm pre-operatively & then twice a day postoperatively for 03 days. In all operations, the gallbladder is removed from the epigastric port without using a retrieval bag by skilled surgeons employing four-port methods and reusable equipment. Most patients had the sub-hepatic tube drain placed and were discharged the day after surgery. RESULTS Acute cholecystitis was the most common operative finding with port-site infection, i.e. 6(42.8%), second being empyema that was seen in 3(21.4%) patients, 2(14.3%) patients had bad adhesions, mucocele in 2(14.3%) patients and thick walled gall bladder with stones was found in 1(7.1%) patients respectively, indicating that the relationship between infection and acute cholecystitis is significant. Regarding the spills of bile, stones, or pus, 3(21.4%) patients had infections despite there being no spillage, while 11(78.6%) patients developed an infection while the spillage happened during their procedures. The p-value was 0.0001, meaning that the spillage might be considered a risk factor for the development of port site infection. CONCLUSION The spilling of bile, stones, or pus, the port of gallbladder removal, and acute cholecystitis are all strongly associated with port site infection. Given that Mycobacterium tuberculosis may be the source of chronic deep surgical site infections, more care should be exercised. The majority of PSIs are superficial and more prevalent in men.